A microwave interferometer for human breath monitoring in proton therapy applications. Issue 2 (1st October 2019) - Donelli, Massimo; Manekiya, Mohammedhusen; Cunial, Davide; Cristoforetti, Luca; Fracchiolla, Francesco
Abstract: In this letter, a microwave continuous‐wave interferometer for monitoring the human breath activity in proton therapy is proposed. The microwave interferometer operates in the K band at 24 GHz, and it can correctly identify the chest movements due to the respiratory activity with the accuracy of a few millimeters. The obtained experimental results show that this system can effectively detect the chest movements with a high degree of accuracy, permitting better synchronization of the proton beam and maximization of the efficacy of the therapy.